1998
DOI: 10.1080/01904169809365546
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of copper toxicity by iron on Spinach physiology

Abstract: The effect of excess copper (Cu) on young spinach (Spinacia oleraced) as well as the role of iron (Fe) for amelioration of toxicity on growth and photosynthesis in Cu-treated plants was evaluated. Plants treated with 160 μM Cu showed symptoms of heavy metal toxicity, while addition of Fe (40 μM) ameliorates to a certain extent toxic effects of Cu, due to antagonistic action between Cu and Fe. Root length and biomass revealed a lower decrease under Cu+Fe than under Cu treatment. Copper accumulation in plant tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 24 publications
4
24
0
Order By: Relevance
“…The analyzer was calibrated with two standard CO 2 /air mixtures. Measurements were made at 25 °C under a photon flux density of about 750 µmol m -2 s -1 (for details see Ouzounidou et al 1998). P N , and E were calculated from gas exchange measurements according to Caemmerer and Farquhar (1981).…”
Section: Methodsmentioning
confidence: 99%
“…The analyzer was calibrated with two standard CO 2 /air mixtures. Measurements were made at 25 °C under a photon flux density of about 750 µmol m -2 s -1 (for details see Ouzounidou et al 1998). P N , and E were calculated from gas exchange measurements according to Caemmerer and Farquhar (1981).…”
Section: Methodsmentioning
confidence: 99%
“…In spinach (Spinacia oleracea L.), 160 μM Cu in the solution culture decreased chlorophyll content by 45 % over control treatment (Ouzounidou et al 1998). Higher Cu (7 and 10 μM) in the nutrient solution decreased photosynthetic pigments in maize plants (Mocquot et al 1996), and 0.5 mM Cu supply in the growth medium decreased chlorophyll contents in cauliflower (Chatterjee and Chatterjee 2000).…”
Section: Effect On Photosynthetic Apparatus and Pigmentsmentioning
confidence: 98%
“…However, in our results, we did not detect any difference in Mg levels and only a slight decrease in calcium content in roots and a small increase in leaves. Mocquot et al (1996) observed an increase in calcium and magnesium levels with increasing copper concentrations in young maize leaves, while Ouzounidou et al (1998) found a decrease in Ca, Mg, Fe, K and Na in both roots and leaves of spinach grown in 0.160 mM copper. Yang et al (2002) reported changes in nutrient uptake both in roots and in shoots of Cu-tolerant Elsholtzia splendens.…”
Section: Discussionmentioning
confidence: 92%